Antioxidant And Anti-Inflammatory Effects Of Ethanolic And Aqueous Root Extracts Of Piliostigma Thonningii (Schumach.) Milne-Redhead - Sylla Tahiri; Dongui Bini Kouamé (European Scientific Journal, ESJ, 2022)
Piliostigma thonningii is a tree with many ethnomedical and medico-religious uses. In Ivory Coast the roots associated with the leaves are used as an antidote for snakebites and for the treatment of gonorrhea and rheumatism. 2,2-Diphenyl 1-picrylhydrazyl is a free radical. This compound is used to measure the antioxidant activity of a plant by its ability to scavenge free radicals from DPPH. Antioxidants help protect our body against free radicals and thus prevent many diseases. The pharmacological importance of Piliostigma thonningii seems to be ignored by a large part of the population. The study of anti-inflammatory activity in vivo which consists of provoking an acute inflammation induced in rats by injection of carrageenan. AEPT and EEPT show significant anti-inflammatory activity. They very significantly inhibit the development of paw edema induced by carrageenan. They significantly reduce the recruitment of immune cells to the inflammatory site. Piliostigma thonningii extracts work by blocking the formation of prostaglandins, the substances responsible for inflammation. The results of study suggest that Piliostigma thonningii possess some antioxidant properties and provide relief against inflammation making it a possible future therapy for inflammation.